A Psychotherapist’s Experience of Self-disclosure, When Practising in the Digital Era: A Heuristic Self-study - Longley, Hannah (Auckland University of Technology, 2021)
Self-disclosure has been a topic of interest since the conception of psychoanalytic practice. Once considered a hindrance to practice, self-disclosure has developed into a tool within the therapist’s toolbox. With the rise of the Internet, resulting in more information readily available and accessible online than ever before, the notion of self-disclosure is changing. This study intends to heuristically explore the phenomenon and experiences of self-disclosure within psychotherapy, in the digital era. Specifically, the therapist’s experience of self-disclosure, alongside how having a digital footprint has influenced and altered self-disclosures within therapeutic relationships, is examined. The intention of this study is to begin to address a gap in a new and emerging field, whilst drawing upon personal experiences and existing research. A heuristic self-study is used to investigate the phenomenon, considering self-inquiry and direct experiences within a larger, societal context, allowing the phases and processes of heuristic inquiry to guide the research. The study intends to provide deeper insight into the lived experiences of the psychotherapist, specifically one whom has a large, revealing online presence; and thus provide a new understanding of how practising in the digital era may impact therapeutic and interpersonal relationships.
Keywords: Self disclosure; Psychotherapy; Heuristic self study; Online